Implementasi Nilai Solidaritas pada Mahasiswa Semester 6 Prodi Pendidikan Bahasa Arab Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta - Muhammad Fikri Hidayat; Hilalludin Hilalludin; Adi Haironi (Student Scientific Creativity Journal, 2024)
Solidarity is a relationship based on shared moral values and collective emotional experiences, crucial for forming social bonds and achieving common goals. This study aims to identify and enhance the implementation of solidarity values among 6th-semester students of Arabic Language Education at Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta. The research employs a qualitative method, with data collected purposively and using the snowball technique, and analyzed inductively. The findings indicate that many students have not yet adopted solidarity values, resulting in a lack of concern for their peers. To address this issue, various steps are proposed, including education and outreach programs, social and cultural activities, cultural festivals, and support from the government and organizations. Principles of solidarity such as care, cooperation, empathy, equality, tolerance, trust, justice, mutual assistance, sacrifice, and patience should be integrated into daily life. Implementing these values is expected to strengthen social bonds, creating a harmonious and supportive environment, and helping students overcome various challenges.